ASEAN-China relations realities and prospects - ASEAN-China Forum 2004 Singapore); Saw, Swee-Hock 1931-.; Sheng, Lijun; Chin, Kin Wah.; Institute of Southeast Asian Studies; Gale Group (Singapore Institute of Southeast Asian Studies, 2005)
"Examines the areas of convergence and divergence in ASEAN-China relations (political, social, and economic) and their possible outcomes."--GVRL description.
An overview of ASEAN-China relations - Saw Swee-Hock, Sheng Lijun and Chin Kin Wah -- Securing a win-win partnership for ASEAN and China - Ong Keng Yong -- China's peaceful development and relations with its East Asian neighbours - Cai Bingkui -- Strengthening cooperation in the ASEAN Regional Forum - Mohamed Jawhat Hassan -- Strengthening ASEAN-China cooperation in the ASEAN Regional Forum - Liu Xuecheng -- ASEAN+3: the roles of ASEAN and China - Eric Teo Chu Cheow -- Ways towards East Asian FTA: the significant roles of ASEAN and China - Zhang Xiaoji -- Japan and the United States in ASEAN-China relations - Herman Joseph S. Kraft -- U.S.-ASEAN, Japan- ASEAN relations and their impacts on China - Cao Yunhua -- India's approach to ASEAN and its regional implications - Hu Shisheng -- The dragon, the bull and the ricestalks: the roles of China and India in Southeast Asia - Chulacheeh Chinwanno -- Evolving security environment in Southeast Asia: an ASEAN assessment - Jusuf Wanandi -- Evolving security environment in Southeast Asia: a Chinese assessment - Han Feng -- China-ASEAN maritime security cooperation: situation and proposals - Wang Zhongchun and Li Yaqiang -- ASEAN-China maritime security cooperation - Michael Richardson -- ASEAN-China FTA: opportunities, modalities and prospects - Shen Danyang -- Building ASEAN-China FTA: opportunities, modalities and prospects - Suthiphand Chirathivat -- China's business environment: a macro economic perspective - Yuwa Hedrick-Wong -- Business environment and opportunities in Shanghai - Zhang Youwen -- Yunnan's Greater Mekong sub-region strategy - He Shengda and Sheng Lijun -- ASEAN-China cooperation for Greater Mekong sub- region development - Kao Kim Hourn and Sisowath Doung Chanto -- South China Sea: turning suspicion into mutual understanding and cooperation - Gao Zhiguo -- The South China Sea disputes after the 2002 Declaration: beyond confidence-building - Aileen S. P. Baviera -- China and ethnic Chinese in ASEAN: post-cold war development - Leo Suryadinata.
Electronic reproduction.
Keywords: ASEAN; National security -- Asia, Southeastern -- Congresses; National security -- China -- Congresses; Electronic books; China -- Foreign economic relations -- Southeast Asia -- Congresses; China -- Foreign relations -- Southeast Asia -- Congresses; Southeast Asia -- Foreign economic relations -- China -- Congresses; Southeast Asia -- Foreign relations -- China -- Congresses; Asia, Southeastern -- Foreign relations -- China -- Congresses; China -- Foreign relations -- Asia, Southeastern -- Congresses